2022
DOI: 10.3389/fmicb.2021.784535
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Microbial Inoculants on Fermentation Quality and Microbiota in Napier Grass (Pennisetum purpureum) and Corn (Zea mays L.) Silage

Abstract: Forage preservation for livestock feeding is usually done by drying the plant material and storing it as hay or ensiling it into silage. During the ensiling process, the pH in the system is lowered by the activities of lactic acid-producing bacteria (LAB), inhibiting the growth of spoilage microorganisms and maintaining the quality of the ensiled product. To improve this process, inoculation of LAB could be used as starter cultures to shorten the ensiling time and control the fermentation process. Here, we com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The LP treatment had the lowest pH and highest lactic acid content of all treatments. It is likely that lactic acid has a lower pH than other organic acids and plays a vital role during fermentation ( Jaipolsaen et al, 2021 ). In this study, the concentration of lactic acid at 30 days was greater ( p < 0.05) than at 60 days of ensiling in all treatments, except for the PA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The LP treatment had the lowest pH and highest lactic acid content of all treatments. It is likely that lactic acid has a lower pH than other organic acids and plays a vital role during fermentation ( Jaipolsaen et al, 2021 ). In this study, the concentration of lactic acid at 30 days was greater ( p < 0.05) than at 60 days of ensiling in all treatments, except for the PA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…. Enterobacter is known to cause silage spoilage (Jaipolsaen et al, 2022). As shown in Tables 5, 7, the addition of LAB is effective in improving silage preservation by increasing the abundance of Lactobacillus, L. buchneri, and L. plantarum.…”
Section: Discussionmentioning
confidence: 99%
“…Inoculation of low-temperature tolerant LAB at ensiling could stimulate favorable fermentation and reconstruct the bacterial community for better preservation of highly moist oat silage nutrients (Chen et al, 2020). Jaipolsaen et al (2022) reported the importance of identifying suitable starter cultures, understanding the natural flora of epiphytic LAB on plants, and applying them together to optimize cost-effective silage production. Among the most used starter cultures of LAB is Lactobacillus plantarum (Keshri et al, 2018;Mu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Applying LAB inoculant (T3) on maize silage during ensiling favoured the dominancy of phylum Bacteroidetes followed by phyla Firmicutes and Proteobacteria. On the contrary, Jaipolsaen et al [48] and Dong et al [49] reported Firmicutes bacteria as the dominant phylum on maize silage treated with LAB inoculant during ensiling. However, other studies reported Proteobacteria as the dominant phylum on silage produced from different forages while treated with LAB inoculant during ensiling [20,27,41].…”
Section: Silage Microbial Composition As Influenced By Additivesmentioning
confidence: 96%